Abraham Lincoln (In Spanish) - Armentrout, David 1962-; Armentrout, Patricia 1960- (Vero Beach, Fla. : Rourke Pub., 2002)
A simple biography of the man who was president during the Civil War.
Includes bibliographical references (p. 24) and index.
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865; Presidents -- Biography -- United States; Presidents; Spanish language materials